Comparison of Serological Test Kits for Diagnosis of Typhoid Fever in the Philippines - Kawano, Razel L. (American Society for Microbiology, 2007)
We evaluated four recent antibody-detection kits for typhoid fever by using 177 febrile patients from our hospital, in 75 of whom Salmonella enterica serotype Typhi grew. TUBEX performed best, achieving 94.7% sensitivity and 80.4% specificity. Typhidot, SD Bioline Typhoid, and Mega Salmonella were less specific and, in most cases, less sensitive.